Clinical Features and Long-Term Outcomes in Very Young Patients with Myocardial Infarction with Non-Obstructive Coronary Arteries - Rahman Ullah, Farooq Ahmad, Mohammad Adeel, Sharafat Hussain, Zeeshan Shoukat, Omer Saqib Gill, (Pakistan Journal of Medical & Health Sciences, 2023)
Background and Aim: The most common cause of acute coronary syndrome (ACS) is the erosion causing the development of atherosclerotic plaque. There is, however, a subset of individuals with ACS-like symptoms but no significant coronary artery obstruction characterized as myocardial infarction with non-obstructive coronary arteries (MINOCA). The purpose of the present study was to assess the clinical features and long-term outcome of young MI patients with non-obstructive coronary arteries. Patients and Methods: This prospective observational study was carried out on 926 patients underwent coronary angiographies in the Cardiology Department of Medical Teaching Institute (MTI) Lady Reading Hospital, Peshawar from January 2019 to December 2022. All the patients (age ≤45 years) with suspected acute coronary syndrome were enrolled. Participants were categorized into three groups: Group-I [obstructive coronary artery disease (o-CAD)], Group-II (MINOCA diagnosed patients), and Group-III [control (non-coronary artery disease)]. Demographic details, clinical features, and outcomes of patients were recorded. Results: Of the total 926 patients underwent coronary angiographies, about 122 (13.2%) patients were ≤45 years old. Out of 122 patients, the incidence of o-CAD, MINOCA, and control (non-coronary artery disease) was 60.7% (n=74), 13.1% (n=16), and 26.2% (n=32) respectively. Chest pain was the most prevalent symptom found in 95.1% (n=116) group-I, 93.8% (n=15) in group-II, and 81.3% (n=26) respectively. MINOCA patients had similar high-density lipoprotein (HDL) and low-density lipoprotein (LDL) cholesterol levels with o-CAD patients, however, the triglyceride values was significantly higher (180.8±90.6) than control (136.2±82.8). Conclusion: The present study found that MINOCA and o-CDA group patients had similar long-term poor outcomes. Triglyceride levels, depression, BMI >30 kg/m2, and family history of CAD are significant risk factors for MINOCA during follow-up. Secondary preventive initiatives are required in these patients to avoid recurrences and enhance outcomes. Keywords: CAD, MINOCA, Young patients, Clinical features, Long-term outcomes